2021
DOI: 10.3390/molecules26133974
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vicinal Difluorination on the Conformation and Potency of Histone Deacetylase Inhibitors

Abstract: Histone deacetylase enzymes (HDACs) are potential targets for the treatment of cancer and other diseases, but it is challenging to design isoform-selective agents. In this work, we created new analogs of two established but non-selective HDAC inhibitors. We decorated the central linker chains of the molecules with specifically positioned fluorine atoms in order to control the molecular conformations. The fluorinated analogs were screened against a panel of 11 HDAC isoforms, and minor differences in isoform sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the paper by Ariawan et al [ 42 ], the effect of vicinal difluorination in the chemical structure of the hydroxamate-based HDACis vorinostat and scriptaid was investigated ( Scheme 11 ). The authors found that the introduction of fluorine substituents does not have a positive effect on the potency to inhibit HDAC.…”
Section: Biological Significance and Purpose Of Fluorination In Hdacismentioning
confidence: 99%
See 2 more Smart Citations
“…In the paper by Ariawan et al [ 42 ], the effect of vicinal difluorination in the chemical structure of the hydroxamate-based HDACis vorinostat and scriptaid was investigated ( Scheme 11 ). The authors found that the introduction of fluorine substituents does not have a positive effect on the potency to inhibit HDAC.…”
Section: Biological Significance and Purpose Of Fluorination In Hdacismentioning
confidence: 99%
“…Even though liquids are easier to handle than gases, it can be considered a disadvantage to work with liquid reagents compared to solids as an alternative. The DexoFluor used for the synthesis of HDACis in the work of Ariawan et al [ 42 ] is subject to this limitation to a certain extent. Fortunately, crystalline solids have now also been described as an improvement on DeoxoFluor for deoxyfluorination [ 97 ].…”
Section: Issues Of Fluorinationmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 , 10 One key advantage of HDAC is their relatively lower rate of side effects. Moreover, most side effects associated with HDAC inhibitors are primarily observed with pan-HDAC inhibitors, 11 indicating that subtype-selective HDAC inhibitor may have fewer adverse effects. Tucidinostat, an oral subtype-selective HDAC inhibitor, received approval from the National Medical Products Administration in China in November 2019 for use in combination with aromatase inhibitors in postmenopausal patients with locally advanced or metastatic breast cancer who have experienced relapse or progression on endocrine therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] The most extensively developed mode of intermolecular alkene difunctionalization is vicinal 1,2-difunctionalization, Figure 1A, for which there are many prominent and useful transformations reported, [12][13][14][15][16][17][18][19][20][21][22] including in the synthesis of complex molecules, such as pharmaceuticals and natural products. [23][24][25][26][27][28] Geminal alkene difunctionalization has also received attention, with several innovative transformations and strategies recently reported in the literature. [29][30][31][32][33][34] This variety of functionalization highlights the versatility of alkenes and their utility in providing access to useful chemical space.…”
mentioning
confidence: 99%